Stakeholders’ perceptions on school feeding programmes’ influence on attendance and dropout rates in Tharaka-Nithi County. African Journal of Education and Practice - Muriungi, Pamella Karambu; Mbijiwe, Jane; Koech, Peter Kibet; M’Rithaa, Mugendi (African Journal of Education and Practice, 2025)
urpose: The purpose of this study was to assess stakeholder’s perceptions on the influence of school feeding programmes on pupil’s attendance and dropout rates in Tharaka Nithi County, Kenya. Methodology: The study adopted a mixed methods approach. The target population for this study was Tharaka Nithi County Education Officials, Headteachers, teachers, and parents of Grade three pupils in public schools. The data collection instruments included: questionnaires, interview guide, observation checklist and focus group discussion guide. Data were analysed using the statistical package for social sciences (SPSS) Version 27. Quantitative data were analysed and presented in the form of frequencies and percentages. The qualitative data were presented in a narrative form in themes. Findings: The study established that stakeholders perceived that: school feeding programs significantly boosted pupils' class attendance; reduced absenteeism; and improved concentration and academic performance, while encouraging consistent school attendance. The schools’ feeding programs significantly reduced pupils dropout rates, and also enhanced academic performance. It was concluded that school feeding programs was perceived to significantly improve pupil attendance and reduced dropout rates. Unique Contribution to Theory, Practice and Policy: The study was anchored on Abrahams Maslow's Hierarchy Theory of Human Motivation. There is need for the County Government and National Governments and NGOS to increase the school feeding programmes in ASAL schools. Vulnerable children in ASAL areas should be given special attention in school feeding programmes. School stakeholders should support the availability of feeding programmes in all the ASAL schools.
Keywords: Dropout Rates; Attendance; School Feeding Programmes